Magnetization Transfer Magnetic Resonance Imaging Noninvasively Detects Renal Fibrosis in Swine Atherosclerotic Renal Artery Stenosis at 3.0 T. Issue 11 (November 2017) - Jiang, Kai; Ferguson, Christopher M.; Woollard, John R.; Zhu, Xiangyang; Lerman, Lilach O.
Abstract : Objectives: Renal fibrosis is a useful biomarker for diagnosis and evaluation of therapeutic interventions of renal diseases but often requires invasive testing. Magnetization transfer magnetic resonance imaging (MT-MRI), which evaluates the presence of macromolecules, offers a noninvasive tool to probe renal fibrosis in murine renal artery stenosis (RAS) at 16.4 T. In this study, we aimed to identify appropriate imaging parameters for collagen detection at 3.0 T MRI and to test the utility of MT-MRI in measuring renal fibrosis in a swine model of atherosclerotic RAS (ARAS). Materials and Methods: To select the appropriate offset frequency, an MT-MRI study was performed on a phantom containing 0% to 40% collagen I and III with offset frequencies from −1600 to +1600 Hz and other MT parameters empirically set as pulse width at 16 milliseconds and flip angle at 800 degrees. Then selected MT parameters were used in vivo on pigs 12 weeks after sham (n = 8) or RAS (n = 10) surgeries. The ARAS pigs were fed with high-cholesterol diet to induce atherosclerosis. The MT ratio (MTR) was compared with ex vivo renal fibrosis measured using Sirius-red staining. Results: Offset frequencies at 600 and 1000 Hz were selected for collagen detection without direct saturation of free water signal, and subsequently applied in vivo. The ARAS kidneys showed mild cortical and medullary fibrosis by Sirius-red staining. The cortical and medullary MTRs at 600 and 1000 Hz were both increased. Renal fibrosis measured ex vivo showed good linear correlations with MTR at 600 (cortex: Pearson correlation coefficient r = 0.87, P < 0.001; medulla: r = 0.70, P = 0.001) and 1000 Hz (cortex: r = 0.75, P < 0.001; medulla: r = 0.83, P < 0.001). Conclusions: Magnetization transfer magnetic resonance imaging can noninvasively detect renal fibrosis in the stenotic swine kidney at 3.0 T. Therefore, MT-MRI may potentially be clinically applicable and useful for detection and monitoring of renal pathology in subjects with RAS. Abstract : Supplemental digital content is available in the text.